2014
DOI: 10.1074/jbc.m113.534859
|View full text |Cite
|
Sign up to set email alerts
|

Coregulator Control of Androgen Receptor Action by a Novel Nuclear Receptor-binding Motif

Abstract: Background:The interaction surface of coactivators and the androgen receptor (AR) is an important target for prostate cancer therapeutics. Results: A new interface formed by binding of the sequence (GARRPR) and the allosteric pocket (BF-3) of the AR has been identified. Conclusion: GARRPR binding modulates AR activity. Significance: The GARRPR/BF-3 interaction is a novel regulatory hub for AR activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 69 publications
0
70
0
Order By: Relevance
“…More recently, the genomic binding profile of AR variants have also been explored and have been shown to compensate for full length AR in an endocrine therapy-like setting [22]. These studies have provided valuable insights in to the molecular biology and function of the AR and have identified several co-activators and corepressors that modulate AR transcriptional activity [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the genomic binding profile of AR variants have also been explored and have been shown to compensate for full length AR in an endocrine therapy-like setting [22]. These studies have provided valuable insights in to the molecular biology and function of the AR and have identified several co-activators and corepressors that modulate AR transcriptional activity [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…This interaction plays an important role in the modulation of AR activity [109,110]. Different binding studies showed that compounds 11 and 14 blocked the interaction of Bag-1L motif peptides with the AR, implying that these compounds binds directly to the AR BF-3 site [103,108]. Taken together, these results show the great potential of the BF-3 site as a therapeutic target for the treatment of CRPC.…”
Section: <Insert Figure 4 (Single Column)>mentioning
confidence: 87%
“…Recent studies have demonstrated the important role of BF-3 in AR signaling regulation through the recruitment of AR coregulators such as FKBP52 [102] and Bag-1L [103] and crosstalk with the adjacent AF-2 [49,104]. Using a crystallographic screening approach, Estébanez-Perpiñá et al were the first to report compounds that allosterically inhibit the interaction of AR with coactivators by binding to the BF-3 site [49].…”
Section: Targeting the Binding Function 3 Sitementioning
confidence: 97%
See 1 more Smart Citation
“…Mutations in NRs can affect the recruitment and activity of coregulators (Chen et al 2005, Duff & McEwan 2005, Prekovic et al 2016. Furthermore, there are also reports of mutations in the coregulators themselves, which also alters their activity in prostate cancer (Chmelar et al 2007, Jehle et al 2014.…”
Section: Nuclear Receptor Coregulator In Prostate Cancermentioning
confidence: 99%